Fengcong, fenglin in shilin - Ravbar, Nataša (Geografski obzornik, 2002)
Although karst researches in China are carried out separately from the karst-sciences of western countries, terms such as fengcong, fenglin and shilin are enforcing gradually into international and Slovene karst terminology. Instead of cone and tower karst Chinese karstologists distinguish two types of tower karst: fengcong and fenglin. Shilin is a type of the subjacent karst. Karren have been transformated into the high pillars and reshaped by rain corrosion. Among them there are deep vertical fractures and trenches.
Keywords: Kitajska; kras (geologija); krasoslovje; kraški pojavi